Dental Students' Soft Drink Consumption and Oral Health Awareness: A Cross-Sectional Knowledge, Attitude, and Practice Study - Jagtap, Chetana; Khandelwal, Saurabh; Patil, Rupali; Jadhav, Avantika; Jadhav, Santosh (Journal of Neonatal Surgery, 2025)
Background: Soft drinks continue to be a preferred beverage among many young people, and their high sugar content and acidity have long been associated with dental caries, enamel erosion, dentin hypersensitivity, and tooth discoloration. Knowledge–attitude–practice (KAP) data on dental students themselves — the very professionals who will one day counsel patients about these habits — remain scarce, especially within dental schools in India. Aim: To characterize the knowledge, attitudes, and practices of dental college students regarding soft drink consumption, and to explore how these self-reported patterns relate to perceived oral health outcomes. Materials and Methods: A cross-sectional survey was carried out among 195 students, ranging from first year through internship, at a single dental teaching institution, using a structured, self-administered questionnaire delivered via Google Forms and covering the knowledge, attitude, and practice domains. Each domain generated a numeric score (Knowledge 0–5; Attitude 0–4; Practice 0–10), which was grouped into poor, average, or good bands. All variables were summarised using descriptive statistics, and the relationship of consumption frequency and academic year to KAP outcomes was examined using chi-square tests, one-way analysis of variance (ANOVA), and Spearman's correlation, with significance set at p<0.05. Results: Of the 195 respondents, 89.7% agreed that soft drinks could be harmful to oral health, and 95.4% recognised their sugar and acid content as a threat to dental tissue; however, only 73.8% recalled receiving formal instruction on this topic. Actual consumption was modest — 62.1% drank soft drinks rarely and 10.3% did not consume them at all, while 7.2% consumed them at least twice weekly. The dental problems most frequently linked to soft drink intake were caries (80.0%), sensitivity (59.0%), and discolouration (49.2%). Mean domain scores were 4.44±0.89 for knowledge (out of 5), 3.23±0.66 for attitude (out of 4), and 6.53±1.48 for practice (out of 10); good knowledge was seen in 88.7% and a favourable attitude in 89.2%, yet only 49.7% reached the “good” practice band. Practice scores differed significantly across consumption-frequency groups (one-way ANOVA, F=39.48, p<0.001), and knowledge showed a modest but significant positive correlation with both practice (Spearman ρ=0.192, p=0.007) and attitude (ρ=0.201, p=0.005). Year of study bore no significant relationship to knowledge category (χ²=4.43, p=0.817) or to composite KAP category (χ²=2.39, p=0.664). ... Conclusion: Dental students in this sample came into the survey already possessing solid knowledge and a broadly protective attitude toward soft drink consumption; however, this did not consistently translate into protective habits such as straw use or rinsing after consumption. The resulting knowledge–practice gap highlights the need for dental curricula that directly target behaviour, alongside broader population-level preventive strategies.